Enhanced 3 dB AR beamwidth metamaterial antenna for nanosatellite payload communication system. Issue 19 (1st September 2018) - Alam, T.; Islam, M.T.; Cho, M.
Abstract : A compact dual‐circular polarised metamaterial inspired antenna is proposed for nanosatellite payload communication. The antenna consists of two‐layered stacked structure with a sandwich rectangular parasitic layer between two layers. Two double negative metamaterial cells. Two unit cells of DNG metamaterial structure are applied inside the pentagonal radiator to enhance 3 dB axial ratio (AR) bandwidth and beamwidth. Two orthogonal feedings are utilised to generate dual‐circular polarisation (CP). The antenna achieves measured 710 MHz (3.06–3.77 GHz) of −10 dB impedance bandwidth with 160 MHz (3.02–3.18 GHz) and 210 MHz (3.05–3.26 GHz) of 3 dB AR bandwidth for port 1 and port 2, respectively. The 3 dB AR beamwidth of 165° for port 1 and 212° for port 2 is exhibited with an average realised gain of 5.15 dB. A 1U nanosatellite structure has been utilised to realise the antenna performance while operation in real‐time environment.